Analisis Motivasi, Profesionalisme Dan Indeppendensi Terhadap Kualitas Audit Aparat Inspektorat Dalam Pengawasan Keungan Daerah(Studi Empiris Pada Kantor Inspektorat KotaSurakarta dan Kabupaten Boyolali) - Alfaizah, Hervani; , Drs. Suyatmin Waskito Adi, M.Si (2015)
This study aimed to examine the effect of motivation, professionalism, and independence on audit quality Inspectorate officials Surakarta and Boyolali. This study uses a quantitative method using primary data obtained from the questionnaire. The population in this study is the auditor who works at the office of the Inspectorate of Surakarta City and County boyolali. The sample used in this study amounted to as much as 40 respondents. Methods of sample collection using Convenience sampling technique. The analysis tool includes the validity and reliability test, normality test, multicollinearity, heteroscedasticity test, regression test, F test and t test. Based on the test results can not be concluded that the effect on the motivation and independence of audit quality, whereas professionalism variable has no effect on audit quality. The F test results show for the variables of motivation, professionalism, and independence together affect the quality of the audit.